2019
DOI: 10.1186/s12885-019-5494-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate cancer predisposing variants by performing whole-exome sequencing on index patients from BRCA1 and BRCA2-negative breast cancer families

Abstract: Background In the majority of familial breast cancer (BC) families, the etiology of the disease remains unresolved. To identify missing BC heritability resulting from relatively rare variants (minor allele frequency ≤ 1%), we have performed whole exome sequencing followed by variant analysis in a virtual panel of 492 cancer-associated genes on BC patients from BRCA1 and BRCA2 negative families with elevated BC risk. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
0
26
0
4
Order By: Relevance
“…Next‐generation sequencing of a cohort of BRCA1 and BRCA2 ‐negative subjects with breast cancer identified a heterozygous HPS6 stop‐loss variant (c.2326T>C, p.*776Arg) in one subject, who also carried heterozygous protein damaging variants in two other genes (Shahi et al, 2019). This variant has not been reported in HPS subjects but is included in Table S4 because it may cause HPS when occurring in a homozygous or compound heterozygous state.…”
Section: Introductionmentioning
confidence: 99%
“…Next‐generation sequencing of a cohort of BRCA1 and BRCA2 ‐negative subjects with breast cancer identified a heterozygous HPS6 stop‐loss variant (c.2326T>C, p.*776Arg) in one subject, who also carried heterozygous protein damaging variants in two other genes (Shahi et al, 2019). This variant has not been reported in HPS subjects but is included in Table S4 because it may cause HPS when occurring in a homozygous or compound heterozygous state.…”
Section: Introductionmentioning
confidence: 99%
“…For BRCA negative families, fine mapping of other high to moderate penetrant breast cancer genes is needed to explain the genetic predisposition to breast cancer. For this purpose, next generation sequencing technologies are widely used as a cost-effective approach for the detection of novel mutations (Shahi et al, 2019). Indeed, target gene sequencing (TGS), whole exome sequencing (WES), and whole genome sequencing (WGS) are the main protocols currently used to identify either new mutations or new candidate genes associated with hereditary disorders (Chandler et al, 2016;Akter et al, 2019;Bewicke-Copley et al, 2019;Posey, 2019;Shahi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor predisposition of Rint1 heterozygous mice indicated a role as tumor suppressor (Lin et al, 2007). Interestingly, genomic studies of human cancers suggested an oncogene or cancer predisposition gene function in glioblastomas, breast cancer and acute myeloid leukemia (Quayle et al, 2012;Park et al, 2014;Shahi et al, 2019;Simonetti et al, 2019). RINT1 mutations were identified in patients of the ALF multisystem developmental disorder (Cousin et al, 2019) and in patients of Lynch syndrome (Park et al, 2014), that often presents retinal pigment epithelium hypertrophy (CHRPE) (Lynch et al, 1987).…”
Section: Discussionmentioning
confidence: 99%